Composition and distribution of corals and macroalgae in Pulau Bidong and the island's proposed management plan - Khor, Hui Min (Fakulti Sains dan Teknologi, 2011)
Pulau Bidong is a small island off the coast of Terengganu, which has been subjected to unregulated development in the past, but it is presently not inhabited. Plans are underway to develop the island as an ecotourism destination and also a stopover for fishermen.Therefore, the objectives of this study were to determine the distribution and abundance of corals, macroalgae and other benthic life forms in the coral reefs, and propose a management plan for the island based on the present and planned activities for the island.The Line Intercept Transect and belt transect methods were used to assess the health of the coral reefs at six stations around Pulau Bidong and one station off Pulau Karah nearby. Overall, the coral cover at Pulau Bidong ranged from fair to excellent, with an average of 46.4% (fair). The two major types of corals found were branching corals of the Family Acroporidae (18.9%), and massive corals (16.8%) of the Families Pontidae and Faviidae. There was also a large proportion of coral rubble covered with algae(24.4%).